1987
DOI: 10.1093/ajcp/87.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Lymphoid Lesions of the Thyroid Gland: Cytopathology by Fine-Needle Aspiration

Abstract: The cytopathologic characteristics of the inflammatory and lymphoid thyroid lesions as seen in fine-needle aspirate smears of 103 patients are reviewed, with emphasis on pitfalls and association with other neoplasms. The cytologic diagnoses were as follows: subacute thyroiditis, 3; Hashimoto's thyroiditis (HT) with or without Hürthle cell nodule, 77; HT and Hürthle cell tumor, 2; HT and follicular neoplasm, 3; HT and papillary carcinoma, 5; lymphoma, 3; HT and nodular colloid goiter, 10. Fourteen patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 0 publications
2
40
1
Order By: Relevance
“…The cytologic literature on SGT is relatively rare, but the cytologic features of SGT has been well described. 1,[4][5][6]10,21 One report summarized the key cytologic features of SGT with performing Giemsa staining. 10 and after that, another report has been published that used Papanicolou stain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytologic literature on SGT is relatively rare, but the cytologic features of SGT has been well described. 1,[4][5][6]10,21 One report summarized the key cytologic features of SGT with performing Giemsa staining. 10 and after that, another report has been published that used Papanicolou stain.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study demonstrate that the cytological diagnosis of SGT can be improved by employing a combination of the typical and constant diagnostic cytological features and immunocytochemical results. 1,[4][5][6] In the early phase of SGT, the typical cytologic findings may be lacking and atypical follicular cells may suggest malignancy. 7 Malignant thyroid lesions can recently be easily diagnosed by immunohistochemical staining in conjunction with using the known molecular markers.…”
Section: 아급성 육아종성 갑상샘염의 세침흡인 세포소견mentioning
confidence: 99%
“…19 Besides the presence of true thyroid nodules (adenomatous, hyperplastic or colloidal nodules), basal inflammatory changes such as fibrotic bands and pseudonodule development may also be seen. 5 No criteria have been established, however, to diagnose and differentiate the two distinct groups of nodules by US. 20 -23 Thus, in cases where there are suspicions of the presence of real nodules, either conservative monitoring or biopsy/surgery might be needed for diagnosis, but both choices have financial and time implications.…”
Section: Yildirim B Gurses B Gurpinar Et Al Sonoelastography Formentioning
confidence: 99%
“…In one retrospective study, the prevalence of cytology-proven Hashimoto thyroiditis appeared to be >10% in patients with thyroid nodules [5]. In addition to the presence of primary thyroid nodules, secondary inflammatory changes such as pseudonodule development may also be observed [6], thereby potentially complicating diagnosis. During an US diagnostic procedure, a unique form of HT, known as focal Hashimoto's thyroiditis (FHT), may present as a lesion mimicking nodular disease in US [7][8][9][10], despite the fact that these previous studies have reported that most nodular Hashimoto thyroiditis commonly appears as solid hyperechoic nodules with ill-defined margins.…”
mentioning
confidence: 99%